CRITICISM OF THE IMPLEMENTATION OF ARTICLE 27 PARAGRAPH(3) OF THE ITE LAW: BETWEEN LEGAL PROTECTION AND CRIMINALIZATION OF EXPRESSION - Samsir Samsir (Adisam Publisher, 2025)
Article 27 paragraph (3) of the Information and Electronic Transactions Law (UU ITE) in Indonesia has become the subject of controversy because it is often used to ensnare individuals who express criticism or opinions in the digital space. This research aims to examine the application of this article through a literature review approach to evaluate the balance between legal protection for individuals and the potential criminalization of freedom of expression. By analyzing statutory regulations, case studies, as well as the views of academics and legal practitioners, this research found that the ambiguity of legal norms in this article opens up space for multiple interpretations that have the potential for misuse. Many cases show that this article is more often used to silence criticism than to protect the public from actual defamation. The legal implications of these findings indicate an urgent need to revise Article 27 paragraph (3) of the ITE Law so that it no longer becomes a tool for criminalizing expression in the digital era. Some recommendations include affirming clearer legal boundaries, applying the principle of ultimum remedium, and prioritizing civil settlement mechanisms or the right to reply before entering the criminal realm. Thus, it is hoped that this policy revision can create a balance between legal protection for individuals and respect for the right to freedom of expression, which is a fundamental principle in democracy.